The clinical and peroperative findings of carcinoma stomach: 61 operated cases (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i2.3865Journal of Chittagong Medical College Teachers' Association 2008: 19(2):16-22